Decision supporting for ship collision avoidance in restricted waters. (21st April 2020) - Zhang, Yuanqiang; Shi, Guoyou; Liu, Hu; Li, Weifeng
To solve the problem of ship collision avoidance in restricted waters, a method is proposed, in this paper, for obtaining the time to the closest point of approach (TCPA), the distance to the closest point of approach (DCPA) and the meeting position considering multileg route, the proposed method considers the turning position and turning time of the ship. For ships with a collision risk, a safe speed can be obtained by setting a new meeting position. The safe speed considers the time elapsed for altering speed. At the end, the proposed method is used to get the collision risk and avoidance measures for three different encounter situations. A navigation simulator is used to verify the avoidance measures. The experimental results show that the proposed algorithm can obtain more accurate results than the existing algorithms.